Brake design and safety - Limpert, Rudolf, 1936- (Society of Automotive Engineers, 2011)
The objectives of this third edition of an SAE classic title are to provide readers with the basic theoretical fundamentals and analytical tools necessary to design braking systems for passenger vehicles and trucks that comply with safety standards, minimize consumer complaints, and perform safely and efficiently before and while electronic brake controls become active.
Title from PDF title page (SAE Web site, 08/15/2012).
Includes index.
Keywords: Automobiles -- Brakes -- Design and construction.; elektronické knihy; electronic books